2015
DOI: 10.1111/bju.13165
|View full text |Cite
|
Sign up to set email alerts
|

Is transperineal prostate biopsy more accurate than transrectal biopsy in determining final Gleason score and clinical risk category? A comparative analysis

Abstract: Objectives To assess the degree of upgrading and increase in clinical risk category of transperineal template biopsy (TTB) compared with transrectal ultrasonography‐guided prostate biopsy (TRUSB). Upgrading of TRUSB Gleason grade and sum after radical prostatectomy (RP) is well recognised. TTB may offer a more thorough mapping of the prostate than TRUSB, as well as a more accurate assessment of the tumour. In this retrospective cohort study of prospectively collected data, we compare the initial TRUSB and TTB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 33 publications
1
20
1
Order By: Relevance
“…Few studies have demonstrated this association. In one recent study, 27 the likelihood of upgrade with transperineal biopsies (30.41%) was less than with TRUS biopsies (33.22%), but the reduction was not statistically significant ( P  = 0.55).…”
Section: Discussionmentioning
confidence: 89%
“…Few studies have demonstrated this association. In one recent study, 27 the likelihood of upgrade with transperineal biopsies (30.41%) was less than with TRUS biopsies (33.22%), but the reduction was not statistically significant ( P  = 0.55).…”
Section: Discussionmentioning
confidence: 89%
“…This changed after several reports of fatalities following septic complications of transrectal biopsy [17]. Image fusion guided TP biopsy is increasingly popular as a mean for accurate diagnosis and risk stratification [11, 18]. An increasing number of studies have showed that MRI/US image-fusion guided TP is an effective and accurate method for prostate cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transperineal prostate biopsy has been becoming an increasingly popular approach for accurate diagnosis and risk stratification of prostate cancer [11]. MRI/US-fusion-guided biopsyis a potential approach to offer improved diagnostic information over systematic 12-core transrectal prostate biopsy guided by TURS alone [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with TR biopsy, TP approach may offer a more aseptic method, with fewer infective complications in light of evidence of fluoroquinolone-resistant bacteria in bowel. However, TP biopsy is a more costly alternative, with longer procedural times and higher risks of acute retention postoperatively (9,10,22,24). In our Department we usually employ a TR approach using an end-fire probe, because we believe that to perform prostate biopsy in the anterior area of the gland it is the most appropriate technique.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, approximately 20-30% of men with CD will require a prostate biopsy within their lifetime, and compared with men non affected, they are at increased risk of developing complications following this procedure (7,8). Although cancer detection rates or the complication rates between transrectal (TR) biopsy and transperineal (TP) biopsy are greatly debated (9,10), in this retrospective study we analysed the use and the safety of transrectal ultrasound-guided prostate biopsy (TRUSBx) in a small cohort of five patients with CD.…”
mentioning
confidence: 99%